Confluence number of certain derivative graphs - Kok Johan; Shiny Joseph (Acta Universitatis Sapientiae: Informatica, 2021)
This paper furthers the study on the confluence number of a graph. In particular results for certain derivative graphs such as the line graph of trees, cactus graphs, linear Jaco graphs and novel graph operations are reported.